Sustaining Engagement during Reading Activities - Fadillah Sandy; Athia Fidian (International Journal of Education, Language, and Religion, 2022)
Research shows that engagement in reading is one of the factors to motivate students’ literacy learning development. The aim of this study is to synthesize and elaborate instructions that enable students’ motivation for being engaged inside and outside classrooms. The method of this study is a literature review using 16 articles. The review was presented in descriptive narration that discusses the multidimensional construct of engagement in reading activities and the instructional strategies to enhance engagement in reading. The results showed that there were not all reading instructions examined in the recent studies represented the entire aspects of engagement. Meanwhile, only a few studies addressed the analysis of those aspects in the reading instruction approach used in the studies.